KESELARASAN GERAK, IRINGAN, DAN BUSANA PADA TARI DEWI SARASWATI - Fatmasari, Intan; Murcahyanto, Hary (TAMUMATRA, 2021)
This study aims to describe the harmony of motion, fashion, and accompaniment to the dance of Dewi Saraswati. The approach used in this study is qualitative method of descriptor. By using the theory of harmony of harmony is conformity, harmony, harmony, and harmony. Data collection techniques using observation techniques, interviews and data collection with documentation. Data analysis used consists of three stages, namely data reduction, display data, and verification. Harmony of motion, fashion, and accompaniment in the dance Dewi Saraswati can be seen in terms of movement using basic motion (variety of motion) Balinese dance has a happy atmosphere with a sweet face nose cerungu (sweet smile), kekuwub (Authority). The accompaniment sound that also has a happy atmosphere, happy with a slow tempo, while because a dancer becomes a figure of Goddess, fashion in addition to being a supporting element of fashion in the dance Dewi Saraswati is in accordance with the history of the Dance Dewi Saraswati. The results of this study describe that harmony in the dance of Dewi Saraswati can be seen from the motion, fashion, and accompaniment in accordance with the history of Dewi Saraswati dance.